NEWS. - Dein, Raymond C. (The Accounting Review, 1962)
This article presents information about the developments related to the field of accounting. South-Western Publishing Co. has announced a $500 annual contribution to the American Accounting Association (AAA) Fellowship Fund. The only stipulation made by South-Western respecting the annual contribution is that grants to individuals from the Fellowship Fund shall not in any way be identified as coming from South-Western Publishing Company. Mr. Eric L. Kohier, former President of the AAA, has been presented a certificate of appreciation and a life membership in the Federal Government Accountants Association. The Small Business Administration has prepared a listing of Management Research Summaries available free on request. The summaries cover a wide variety of subjects in the broad areas of managing, financing, and operating small business enterprises. The National Association of Accountants has announced special recognition awards offered for research essays written on the topic "Choosing Accounting Practices For Reporting To Management."